First Identification and Genetic Characterization of a Novel Duck Astrovirus in Ducklings in China - Zhang, Junqin; Huang, Yunzhen; Li, Linlin; Dong, Jiawen; Kuang, Ruihuan; Liao, Ming; Sun, Minhua (Frontiers in Veterinary Science, 2022)
Four divergent groups of duck astroviruses (DAstVs) have been identified that infect domestic ducks. In March 2021, a fatal disease characterized by visceral urate deposition broke out in 5-day-old Beijing ducks on a commercial farm in Guangdong province, China. We identified a novel duck astrovirus from the ducklings suffering from gout disease. The complete genome sequence of this DAstV was obtained by virome sequencing and amplification. Phylogenetic analyses and pairwise comparisons demonstrated that this DAstV represented a novel group of avastrovirus. Thus, we designated this duck astrovirus as DAstV-5 JM strain. DAstV-5 JM shared genome sequence identities of 15–45% with other avastroviruses. Amino acid identities with proteins from other avastroviruses did not exceed 59% for ORF1a, 79% for ORF1b, and 60% for ORF2. The capsid region of JM shared genetic distances of 0.596 to 0.695 with the three official avastrovirus species. suggesting that JM could be classified as a novel genotype species in the Avastrovirus genus. Meanwhile, JM shares genetic distances of 0.402–0.662 with all the other known unassigned avastroviruses, revealing that it represents an additional unassigned avastrovirus. In summary, we determined that the DAstV-5 JM strain is a novel genotype species of avastrovirus.